Aplastic Anemia Associated with Oral Terbinafine: A Case Report and Review of the Literature - ATAGÜNDÜZ, IŞIK; TÜRKÖZ, HÜSEYİN KEMAL (GALENOS YAYINCILIK, 2014)
Onychomycosis (OM) is a common fungal infection of the toenails and/or fingernails that is highly prevalent in the general population and also responsible for significant morbidity. OM is caused by dermatophytes, nondermatophytic molds, or yeast. Today systemic antifungal agents are considered as the gold standard for all types of OM. Here we report a case of aplastic anemia associated with oral terbinafine use and a review of the literature on hematological toxicities associated with terbinafine.
Keywords: Onychomycosis; Terbinafine; Aplastic anemia; Hematological toxicity; Pancytopenia; Adverse events; RESISTANCE P-GLYCOPROTEIN; POSTMARKETING SURVEILLANCE; AGRANULOCYTOSIS; ONYCHOMYCOSIS; NEUTROPENIA; UPDATE; CELLS